2021
DOI: 10.1177/18479790211017353
|View full text |Cite
|
Sign up to set email alerts
|

Solving the multi-level location routing problem considering the environmental impact using a hybrid metaheuristic

Abstract: The multi-level location routing problem (MLLRP) is an extension of the capacitated location routing problem (CLRP). MLLRPs are considered a class of combinatorial optimization problems that arise in transportation applications, such as agricultural logistic planning. Along with concerns regarding the environmental harmfulness, recent studies have considered “green” logistics. This paper addressed a low environmental impact model for MLLRP by considering characteristics, emissions, and traffic congestion that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Moreover, the negative social impact was overlooked in these studies. Lastly, substantial differences in model constraints exist between the current proposed model and the models in the articles of Theeraviriya et al [64] and [65]. conflicting sustainable goals.…”
Section: Literature Reviewmentioning
confidence: 96%
See 3 more Smart Citations
“…Moreover, the negative social impact was overlooked in these studies. Lastly, substantial differences in model constraints exist between the current proposed model and the models in the articles of Theeraviriya et al [64] and [65]. conflicting sustainable goals.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Less closely related research works are found in studies conducted by Theeraviriya et al [64] and [65], which addressed the LRP in the palm oil supply chain. Theeraviriya et al [64] focused on a singleechelon network involving palm oil fields and palm oil collection centers.…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…Environmental and sustainable energy is a critical topic. CO 2 emissions into the atmosphere are strongly related to energy consumption in human activities; they are generated by traditional fuels from natural resources which are becoming depleted [44]. Liu [39] studied scheduling problems that were related to an environment where the objective of minimizing CO 2 emissions was investigated with total weighted tardiness (TWT).…”
Section: Literature Reviewmentioning
confidence: 99%